Penerapan Teknik Simulasi untuk Efisiensi Proses Bongkar Muat Kapal pada Industri Maritim - Manungku Trinata Pramudita; Iie Suwondo; Iwan Kurniawan (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2025)
The loading and unloading process is one of the most vital activities in port operations and plays a significant role in ensuring the smooth flow of national logistics. However, in practice, various forms of inefficiency are still frequently encountered, such as high ship waiting times, low utilization of loading and unloading equipment, and imbalances in labor scheduling and cargo flow in the yard area. These conditions increase turnaround times and hinder port productivity. To address these issues, an analytical approach is needed that can comprehensively model system behavior so that the causes of inefficiency can be precisely identified and tested through improvement scenarios without disrupting actual operations. This study aims to analyze the efficiency level of the ship loading and unloading process at the Port of Tanjung Emas Semarang by applying the Discrete Event Simulation (DES) method using Arena software. The model was developed to describe the flow of activities from ship arrival, through the service process using cranes, to the distribution of cargo to the storage area. Model validation was carried out by comparing simulation results with actual data. The results showed that the combination scenario of adding cranes and adjusting shift schedules provided the most significant efficiency improvement, with a reduction in ship dwell time of up to 20%, waiting time of up to 30%, and an increase in crane utilization of up to 83%. These findings confirm that DES is effective as an analytical tool and basis for operational decision-making at ports.